LncRNA-SUMO3 and lncRNA-HDMO13 modulate the inflammatory response by binding miR-21 and miR-142a-3p in grass carp. (August 2021) - Li, Liuyang; Jia, Xuewen; Liu, Yang; He, Yan; Pang, Yifan; Shen, Yubang; Xu, Xiaoyan; Li, Jiale
Abstract: Septicemia is a systemic inflammatory response to bacterial infection in grass carp ( Ctenopharyngodon idella ). It could lead to lethality. There is increasing evidence that long noncoding RNAs are involved in the regulation of inflammatory response. In the present study, we firstly confirmed that lncRNA-SUMO3 and lncRNA-HDMO13 could involve in the inflammatory response following infection with Aeromonas hydrophila . Dual-luciferase reporter assays and lncRNA expression profiling confirmed that lncRNA-SUMO3 and lncRNA-HDMO13 contains a functional miR-21 and miR-142a-3p binding site. Meanwhile, transfection with lncRNAs mimics and inhibitors affected the expression of miRNAs and its target genes, including jnk, ccr7, glut3 and tnfaip2 . Moreover, the downstream proinflammatory factors of miR-21 and miR-142a-3p were also regulated by lncRNA-SUMO3 and lncRNA-HDMO13. Our results provide a theoretical basis for exploring the molecular mechanism of grass carp lncRNAs regulating inflammation. Highlights: lncRNA-SUMO3 and lncRNA-HDMO13 are upregulated following Aeromonas hydrophila infection. Downregulation of lncRNA-SUMO3 and lncRNA-HDMO13 depress proinflammatory cytokine expression. miR-21 and miR-142a-3p were regulated by lncRNA-SUMO3 and lncRNA-HDMO13. lncRNA-SUMO3 and lncRNA-HDMO13 effect on the target genes of miR-21 and miR-142a-3p.